Beethoven and the lyric impulse : essays on Beethoven song - Glauert, Amanda (Abingdon, Oxon : Routledge, 2021)
Amanda Glauert revisits Beethoven's songs and studies his profound engagement with the aesthetics of the poets he was setting, particularly those of Herder and Goethe. The book offers readers a rich exploration of the poetical and philosophical context in which Beethoven found himself when composing songs. It also offers detailed commentaries on possible responses to specific songs, responses designed to open up new ways for performing, hearing and appreciating this provocative song repertoire. This study will be of great interest to researchers of Beethoven; German song; aesthetics of words and music.
OCLC-licensed vendor bibliographic record.
Keywords: Beethoven, Ludwig van, -- 1770-1827.; Songs, German -- 19th century -- History and criticism; MUSIC / Genres & Styles / Opera; HISTORY / Europe / Germany; SOCIAL SCIENCE / Anthropology / Cultural